Palliative Care Practice in Neurocritical Care - Knies, Andrea K.; Hwang, David Y. (Seminars in Neurology, 2016)
Many neurocritically ill patients and their families have high amounts of palliative care needs. Multiple professional societies relevant to neurocritical care have released consensus statements on meeting palliative care needs in neuroscience intensive care units. In this review, the authors discuss the ongoing debate regarding what model of palliative care delivery is optimal, focus on the process of shared decision making during goals-of-care discussions, and briefly comment on transitions from intensive care to comfort care. Regardless of an institution's model of palliative care practice, every neurocritical care clinician should possess core competencies necessary to provide basic, integrative palliative care for neurocritically ill patients. Given the high proportion of neurocritically ill patients who lack decision-making capacity, communication skills that enable clinicians to facilitate shared decision making with patients' surrogates are of particular relevance, especially when the limitation of life support is in the discussion. High-quality decision aids to assist neurocritical care teams and surrogate decision makers during common goals-of-care discussions may have the potential for further promotion of best palliative care practices.
Keywords: critical care; palliative care; shared decision making; end-of-life care